CFD optimization of feedstock injection angle in a FCC riser. (22nd October 2016) - Chen, Sheng; Fan, Yiping; Yan, Zihan; Wang, Wei; Liu, Xinhua; Lu, Chunxi
Abstract: Feedstock injection zone is a key section for fluid catalytic cracking (FCC) riser reactor. In conventional design of commercial FCC risers, the injection angle of the feedstock is 30° upward with the riser axis, which is found to easily cause nonuniform oil-catalyst contact and severe back-mixing in the feedstock injection zone. In this work, the effect of feedstock injection angle is investigated by performing 3-D simulations with seven injection configurations including three inclined upward, one horizontally and three inclined downward. The two-fluid model (TFM) and the energy-minimization multi-scale (EMMS) drag is combined in simulations. Comparison with experimental data is conducted in terms of the profiles of solids and feed volume fractions. Several variables including the backflow ratio, the radial nonuniformity index and the mean residence time of feed, are further introduced to quantify the hydrodynamic dependence of flow and mixing on the injection settings. It is found that the downward injection schemes are better to realize uniform mixing and matching between catalysts and feed than the upward injection schemes. A 30° downward injection angle is desired to improve the distributions of catalysts and feed, reduce the catalyst-feed contacting time and eliminate the effect of secondary flow on severe back-mixing near the riser wall. Graphical abstract: Highlights: Downward injection is better to realize even mixing in the feedstock injection zone. The effect of secondary flow on back-mixing is eliminated with downward injection. The 30° downward angle is the best option to realize the desired flow and mixing.